Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/brain/awh648
|View full text |Cite
|
Sign up to set email alerts
|

Brain motor system function after chronic, complete spinal cord injury

Abstract: Most therapies under development to restore motor function after spinal cord injury (SCI) assume intact brain motor functions. To examine this assumption, 12 patients with chronic, complete SCI and 12 controls underwent functional MRI during attempted, and during imagined, right foot movement, each at two force levels. In patients with SCI, many features of normal motor system function were preserved, however, several departures from normal were apparent: (i) volume of activation was generally much reduced, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
161
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(184 citation statements)
references
References 59 publications
(72 reference statements)
18
161
1
3
Order By: Relevance
“…Whether these results hold for brain damaged patients with a full loss of motor control remains to be tested. Promising evidence comes from patients suffering from complete spinal cord injury who despite their chronic state still demonstrate motor system activation in response to attempted overt movement (Cramer et al, 2005;Hotz-Boendermaker et al, 2008).…”
Section: Motor Executionmentioning
confidence: 99%
“…Whether these results hold for brain damaged patients with a full loss of motor control remains to be tested. Promising evidence comes from patients suffering from complete spinal cord injury who despite their chronic state still demonstrate motor system activation in response to attempted overt movement (Cramer et al, 2005;Hotz-Boendermaker et al, 2008).…”
Section: Motor Executionmentioning
confidence: 99%
“…This dynamic compensatory mechanism likely represents an adaptive remodeling response designed to preserve neurological function. Although the majority of functional neuroimaging studies have demonstrated this neuroplasticity in cerebral pathological conditions, the results of recent laboratory investigations have demonstrated that cortical reorganization can occur in response to injury to ascending and descending fiber tracts within the spinal cord 4,7,11,[19][20][21][22][23] .In this article we describe a novel method of assessing cortical representational maps for hand and foot activity in patients with CSM by using fMR imaging. In the pilot study described, we investigated the cortical plasticity in patients with CSM as a result of chronic spinal cord injury, as well as subsequent reorganization following decompression surgery.…”
mentioning
confidence: 98%
“…35 Not many studies have correlated the postoperative motor improvement with plasticity. 19 Some studies have shown adaptive changes in bilateral primary motor cortex (M1), supplementary motor area (SMA), premotor area (PMA), cingulate motor area, parietal cortex, and contralateral primary somatosensory cortex (S1) in cases of SCI [8][9][10][11][27][28][29]33,40 and cervical compressive myelopathy due to spondylosis. 13,14,23,38 In this study we aimed to understand the cortical changes that occur due to CSM and following CSM surgery and to correlate these changes with functional recovery by using functional MRI (fMRI).…”
mentioning
confidence: 99%